Evaluation of Thermophysical Properties of Functionalized Imidazolium Thiocyanate Based Ionic Liquids - Gonfa, G. (American Chemical Society, 2015)
New cyano-based ionic liquids with thiocyanate anion and nitrile, ally, benzyl, and hydroxyl functionalized imidazolium cations were prepared, and some of their important thermophysical properties were measured. Properties such as density, viscosity, and refractive index were measured over various temperature ranges. From the experimental density values, the molecular volume, standard molar entropy, lattice energy, and thermal expansion coefficient of the ionic liquids were calculated. The thermal stabilities of the ionic liquids were investigated using thermogravimetric analysis. The effects of functionalized imidazolium side chains on the thermophysical properties of the ionic liquids were investigated. Density functional theory calculations were performed to study the effect of the structural variation of the imidazolium cation on properties of the ionic liquids. Â© 2015 American Chemical Society.